Numerical Simulation of light propagation in silver nanowire films using time-harmonic inverse iterative method - Yan, Shuai; Krantz, Johannes; Forberich, Karen; Pflaum, Christoph; Brabec, Christoph (Journal of Applied Physics, 2013)
The interaction between light and silver nanowires (Ag NWs) in a thin film is simulated by solving Maxwells equations numerically. Time-harmonic inverse iterative method is implemented to overcome the problem of negative permittivity of silver, which makes the classical finite-difference time-domain iteration unstable. The method is validated by showing the correspondence between the plasmonic resonance of an Ag NW from a two dimensional simulation and the analytical solution. In agreement with previous experimental studies, the simulation results show that the transmissivity of the Ag NW films is higher than expected from the geometric aperture. The cause of this phenomenon is studied using TE/TM modes analysis for Ag NW films with different surface coverage of parallel-aligned Ag NWs. Furthermore, 3D simulation of Ag NW films with randomly arranged Ag NWs is performed by parallel computation on high performance computers. A binder layer is taken into account for a preliminary comparison between the simulation and experimental results. The agreements and disagreements between the simulated and measured spectra are discussed. © 2013 AIP Publishing LLC.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.c3sim.numeri
Keywords: Finite difference time domains; High performance computers; Negative permittivity; Parallel Computation; Plasmonic resonances; Silver nanowires; Surface coverages; Two-dimensional simulations Engineering controlled terms: Computer simulation; Electric resistance measurement; Finite difference time domain method; Inverse problems; Iterative methods Engineering main heading: Silver